Management of legal compliance in occupational health and safety. A literature review. - Salguero-Caparrós, Francisco Miguel; Pardo-Ferreira, María del Carmen; Martínez-Rojas, María; Rubio-Romero, Juan Carlos (Elsevier, 2019)
Occupational health and safety legislation is an essential part of the process to manage organisations and companies. However, there are criticisms that the regulation of occupational health and safety could be restricting the impulses of innovation and industrial development. This has led to proposals to repeal regulations to reduce the regulatory burden when possible. This work aims to delve into the difficulties that organisations encounter in their attempts to comply with occupational health and safety legislation and manage the process effectively. A systematic review was conducted of published studies that have analysed the relationship between occupational health and safety (OHS) management and compliance with legislation, regulations and rules. The search for relevant publications mainly used international bibliographic databases and scientific search engines. Quotes from other authors were also examined. This review provides knowledge on how compliance and noncompliance with legislation influences daily health and safety management in companies. The review highlights and discusses both successful regulatory strategies and the main difficulties, weaknesses, limitations and challenges companies face when adopting and complying with these regulations. This study concludes that management of legal compliance in companies, particularly in small and medium-sized enterprises has become a complicated task. Management of occupational health and safety systems should not only be based on prescriptive principles and the detection of non-compliance, but also on proactive principles including an examination of how legal compliance affects daily performance.
Keywords: Seguridad industrial - Legislación; Higiene industrial - Legislación; Reglamentos de seguridad; Occupational Health and Safety; Legislation; Legal compliance; Safety rules; Safety regulation; Review